L’ascension de l’artiste dans The Mountain and the Valley (1952) d’Ernest Buckler - André Dodeman (Revue de Géographie Alpine)
With his first novel, The Mountain and the Valley (1952), Canadian writer Ernest Buckler chose to stay true to the longstanding tradition of the Künstlerroman, best illustrated by one of the greatest modernist writers of the twentieth century, James Joyce and his A Portrait of the Artist as a Young Man (1916). Like Joyce who chose to revisit the genre, Buckler decided to write about the throes of a young artist who seeks to escape from tradition and life in the country. The Mountain and the Valley relates the intellectual coming of age of David Canaan, a young character whose artistic sensitivity sets him apart from the rest of his community in the Annapolis Valley, a valley in the Nova Scotian hinterland of Canada. The story is set in the small town of Entremont which, as its very name suggests, is surrounded by two mountains that isolate and confine the characters to a life of routine and deny them access to time and progress. The North and South Mountains do not merely enclose the characters in the seasonal life of the farmer, they frame the narrative of David Canaan that begins and concludes with the ascent of the South Mountain where he dies prematurely at the age of thirty. This article will study the relationship between the image of the mountain, the plotline and the very act of writing itself as a creative process that the writer constantly interrogates. Is writing the only way to represent the emergence and uniqueness of a writer who is awakening to his own consciousness? I will try to explain how the mountain not only shapes the novel, but also a text made salient through contact with a seeming monolithic mountain. As a result, salience will be understood as the emphasis laid on the artist’s awakening, an awakening that cannot be studied separately from the geographical space the protagonist inhabits. Relief-related discourse will inevitably lead to discourse related to the awakening to one’s own consciousness.